El análisis del viraljacking y la percepción del peruano millennial: El Juego del Calamar - Quijandría Cayo, Eliana Alejandra (2023)
It describes the transition from the newsjacking technique to becoming the viraljacking technique, which consists of using events related to audiovisual productions, musical themes, and occurrences, most of which are covered by journalism. The technique arises due to the persistence of these events over time and their level of trendiness on social media. This research takes a qualitative approach, basing its analysis on the Theory of Advertising Appeals and Needs, identifying the characteristics of the advertising format and the use of visual rhetorical figures. The case study focuses on the series ‘Squid Game’ due to its popularity on social media, aiming to understand the perceptions of Peruvian consumers based on their experience with viraljacking. It concludes that the technique significantly benefits brands in terms of message recall and comprehension, and that users value the wit, sense of humor, and the technique’s ability to communicate the message briefly.